2006
DOI: 10.1111/j.1470-6431.2006.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

In search of fair trade: ethical consumer decision making in France

Abstract: While the market for fair trade products has been growing in many countries, this paper examines the French market where fair trade remains marginal but is experiencing growth. Using a modified Theory of Planned Behaviour framework the research examines consumer intention to purchase fair trade grocery products in order to explain the pertinent decision‐making criteria of both consumers of and potential consumers of fair trade. Results reveal that concerned consumers should not be treated as one homogeneous gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
162
1
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 200 publications
(188 citation statements)
references
References 29 publications
8
162
1
7
Order By: Relevance
“…In their study of 1600 households in Devon, UK, Gilg, Barr and Ford (2005) found that people could be categorized by a combination of two behavioral considerations: the kinds of activities that they undertook and how often (or consistently, see below) they performed these activities. Other studies center on how often people undertake the same activity (Chan 1999;Ozcaglar-Toulouse, Shiu and Shaw 2006), how consistently they behave (Neilssen and Scheepers 1992;Peattie 2001) or whether they undertake a few (different) activities or carry out a wide range of green or ethical activities (McDonald and Oates 2006). Studies that assess a range of different kinds of activities or look at use and disposal as well as point of purchase offer a richer picture of green or ethical consumption than single issue studies on the purchase of fair trade items, or recycling behavior, for example, would allow.…”
Section: Grouping Individuals Using Behavioral Constructsmentioning
confidence: 99%
“…In their study of 1600 households in Devon, UK, Gilg, Barr and Ford (2005) found that people could be categorized by a combination of two behavioral considerations: the kinds of activities that they undertook and how often (or consistently, see below) they performed these activities. Other studies center on how often people undertake the same activity (Chan 1999;Ozcaglar-Toulouse, Shiu and Shaw 2006), how consistently they behave (Neilssen and Scheepers 1992;Peattie 2001) or whether they undertake a few (different) activities or carry out a wide range of green or ethical activities (McDonald and Oates 2006). Studies that assess a range of different kinds of activities or look at use and disposal as well as point of purchase offer a richer picture of green or ethical consumption than single issue studies on the purchase of fair trade items, or recycling behavior, for example, would allow.…”
Section: Grouping Individuals Using Behavioral Constructsmentioning
confidence: 99%
“…So far, the dominant approach to increasing the amount of variance explained in ethical intentions or behavior has been the addition of variables that may have an effect alongside established attitudinal 4 constructs. For example, in applying the TPB to ethical consumer behavior, Shaw and colleagues (Ozcaglar-Toulouse et al, 2006;Shaw and Clarke, 1999;Shaw and Shiu, 2002a, 2002b, 2003Shaw et al, 2000) suggest the addition of personal norm and self-identity. However, empirical research is lacking on various other key factors that have since appeared in the literature (Andorfer and Liebe, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the sustainable or ethical marketing literature, the joint examination of personal and social norms has received less attention, although work by Shaw and colleagues examined the effects of subjective norms and a construct similar to personal norms, ethical obligation, on intention to purchase fair trade grocery products. Their studies show mixed effects as well (Ozcaglar-Toulouse et al 2006;Shiu 2002, 2003;Shaw et al 2000). In further support of our research on the effects of personal and social norms on sustainable consumer behavior are the suggestions by Vitell (2015), who argues that future research should focus on identifying the characteristics of people who are socially responsible and of those who are not, as well as the influence of family and friends on ethical decision making.…”
Section: Introductionmentioning
confidence: 69%